Feasibility of a twitter campaign to promote HPV vaccine uptake among racially/ethnically diverse young adult women living in public housing. - Allen, Jennifer D.; Hollander, Justin.; Gualtieri, Lisa.; Alarcon Falconi, Tania M.; Savir, Stephanie.; Agénor, Madina. (Tufts University. Tisch Library., 2020)
Keywords: Human papilloma virus, Vaccination, Health communication, Twitter, Low-income, Public housing.; Springer Open.